2021
DOI: 10.3390/brainsci11081000
|View full text |Cite
|
Sign up to set email alerts
|

Change in Blood Flow Velocity Pulse Waveform during Plateau Waves of Intracranial Pressure

Abstract: A reliable method for non-invasive detection of dangerous intracranial pressure (ICP) elevations is still unavailable. In this preliminary study, we investigate quantitatively our observation that superimposing waveforms of transcranial Doppler blood flow velocity (FV) and arterial blood pressure (ABP) may help in non-invasive identification of ICP plateau waves. Recordings of FV, ABP and ICP in 160 patients with severe head injury (treated in the Neurocritical Care Unit at Addenbrookes Hospital, Cambridge, UK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Therefore, it is necessary to expand the scope of TBI research. Interestingly, a 2021 study found that [ 25 ] the “Dissimilarity/Difference Index” (DI) between transcranial Doppler flow velocity (FV) and arterial blood pressure (ABP) waveforms appears to be more robust than conventional pulsatility indices. Distinguish between ICP plateau waves and baseline episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to expand the scope of TBI research. Interestingly, a 2021 study found that [ 25 ] the “Dissimilarity/Difference Index” (DI) between transcranial Doppler flow velocity (FV) and arterial blood pressure (ABP) waveforms appears to be more robust than conventional pulsatility indices. Distinguish between ICP plateau waves and baseline episodes.…”
Section: Discussionmentioning
confidence: 99%